2019
DOI: 10.1371/journal.pone.0222458
|View full text |Cite
|
Sign up to set email alerts
|

Trends in maternal prepregnancy body mass index (BMI) and its association with birth and maternal outcomes in California, 2007–2016: A retrospective cohort study

Abstract: ObjectiveTo determine recent trends in maternal prepregnancy body mass index (BMI) and to quantify its association with birth and maternal outcomes.MethodsA population-based retrospective cohort study included resident women with singleton births in the California Birth Statistical Master Files (BSMF) database from 2007 to 2016. There were 4,621,082 women included out of 5,054,968 women registered in the database. 433,886 (8.6%) women were excluded due to invalid or missing information for BMI. Exposures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 60 publications
1
49
1
Order By: Relevance
“…Xie [25] found that excessive GWG increased neonatal birth weight, but no relationship was found between pre-pregnancy BMI and birth weight. However, Ratnasiri [26] conducted a retrospective cohort study, and the results showed prepregnancy overweight and obese contributed to a lower SGA rate and pre-pregnancy underweight decreased the risk of LGA. These differences may be attributed to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Xie [25] found that excessive GWG increased neonatal birth weight, but no relationship was found between pre-pregnancy BMI and birth weight. However, Ratnasiri [26] conducted a retrospective cohort study, and the results showed prepregnancy overweight and obese contributed to a lower SGA rate and pre-pregnancy underweight decreased the risk of LGA. These differences may be attributed to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal prepregnancy obesity and smoking during both first and second trimesters of pregnancy that affected health outcomes were described before [ 14 , 15 ]. The maternal pre-pregnancy body mass index (BMI) (weight in kg/height in m 2 ) was categorized using World Health Organization (WHO) criteria as: BMI <18.5 kg/m 2 , underweight; BMI 18.5–24.9 kg/m 2 , normal weight; BMI 25.0–29.9 kg/m 2 , overweight; BMI 30.0–34.9 kg/m 2 , class I obesity; BMI 35.0–39.9 kg/m 2 , class II obesity; and BMI > 40 kg.m 2 , class III obesity.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, analysis of data from the birth files reported that the rates of pre-pregnancy overweight and obesity were steadily rising in California during the period 2007-2016 [15]. During the study period of 2007-2015, 55% of infant deaths in California were to mothers who were overweight or obese before pregnancy.…”
Section: Maternal Overweight and Obesitymentioning
confidence: 99%
“…Maternal pre-pregnancy obesity is independently associated with fetal overgrowth and with total body adiposity, abdominal fat accumulation, and lower fat free-mass in neonates [ 23 , 24 , 25 , 26 , 27 , 28 ]. These features are aggravated by an excessive GWG during mid and late pregnancy at the time of higher fat accretion in the fetus [ 25 , 29 , 30 ].…”
Section: Maternal Obesity and Its Consequences For The Offspringmentioning
confidence: 99%